GE_GERICHTE P/909/2018 vom 3. Dezember 2018 - GE Cour de justice (2018)
FIXATION DE LA PEINE ; CONCOURS D'INFRACTIONS ; DÉFENSE D'OFFICE ; INDEMNITÉ(EN GÉNÉRAL) | LEtr.115.al1.leta; LEtr.115.al1.letb; CP.49.al2; CP.286.al1; LStup.19.al1; CP.47; LStup.19a.al1; CPP.428; CPP.135.al1